PENGARUH JUMLAH PENDUDUK MISKIN, JUMLAH PENGANGGURAN, BELANJA PEMERINTAH SEKTOR PENDIDIKAN DAN KESEHATAN TERHADAP KESEJAHTERAAN MASYARAKAT DI KABUPATEN SAMBAS - Suradi, Romi; Ayulestari, Isna; Dhayan, Hana (Jurnal Ekonomi dan Manajemen, 2025)
This study aims to examine and analyze the influence of the number of poor people, the number of unemployed, government spending on the education sector, and the health sector on community welfare as measured by the Human Development Index (HDI) in Sambas Regency. This research employs a descriptive quantitative approach, utilizing secondary data obtained from the Central Statistics Agency (BPS) and the Directorate General of Financial Balance of the Ministry of Finance. The data used is time series data covering the last 15 years, from 2010 to 2024. The analytical method employed is multiple linear regression. The results show that the number of poor people has a negative but not significant effect on people's welfare. The number of unemployed has a positive but not significant effect on community welfare. Government spending on health has a positive but not significant effect on people's welfare. Government spending on education has a positive and significant effect on community welfare in Sambas Regency. These findings suggest that educational investment plays a crucial role in improving human development outcomes, while poverty, unemployment, and health spending require more comprehensive policy interventions to achieve significant impacts on welfare.